Study of the influence of yogurt starters on the process of goat’s and cow’s milk fermentation in different ratios - J. S. Shmidt; A. D. Lodygin; S. A. Emelyanov (Современная наука и инновации)
The purpose of the research is to study the effect of yogurt cultures on the efficiency of the goat milk fermentation process. The objects of research were goat's milk, cow's milk and starter cultures Bifidonorm from Lactoferm ECO (Italy) and bioprox YO-PROX 569 (France). The relevance of obtaining functional fermented dairy products based on goat's milk is substantiated. The optimal dosage of starter cultures in the production of yogurt based on goat's milk has been established. The effect of starter cultures on the fermentation process during fermentation of goat's and cow's milk in various ratios was studied. The possibility of using Bifidonorm and bioprox YO-PROX 569 starter cultures for the production of yogurt based on goat's milk has been confirmed. The relevance of functional fermented dairy products based on goat's milk obtaining is substantiated. The process of goat's and cow's milk mixtures fermentation was studied at their different ratio using two types of starter cultures. The influence of the direct vat set starter culture type on the organoleptic and physico-chemical parameters of yogurt based on goat's milk was studied. The possibility of goat’s milk using for the manufacturing of fermented dairy products has been confirmed.